Verbal fluency functional magnetic resonance imaging detects anti‐seizure effects and affective side effects of perampanel in people with focal epilepsy. Issue 2 (8th January 2023) - Xiao, Fenglai; Caciagli, Lorenzo; Wandschneider, Britta; Fleury, Marine; Binding, Lawrence; Giampiccolo, Davide; Hill, Andrea; Galovic, Marian; Foong, Jaqueline; Zhou, Dong; Sander, Josemir W.; Duncan, John S.; et al.
Abstract: Perampanel, a noncompetitive antagonist of the postsynaptic a‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic (AMPA) receptor, is effective for controlling focal to bilateral tonic–clonic seizures but is also known to increase feelings of anger. Using statistical parametric mapping–derived measures of activation and task‐modulated functional connectivity (psychophysiologic interaction), we investigated 14 people with focal epilepsy who had verbal fluency functional magnetic resonance imaging (fMRI) twice, before and after the add‐on treatment of perampanel. For comparison, we included 28 people with epilepsy, propensity‐matched for clinical characteristics, who had two scans but no change in anti‐seizure medication (ASM) regimen in‐between. After commencing perampanel, individuals had higher task‐related activations in left orbitofrontal cortex (OFC), fewer task‐related activations in the subcortical regions including the left thalamus and left caudate, and lower task‐related thalamocaudate and caudate‐subtantial nigra connectivity. Decreased task‐related connectivity is observed between the left OFC and precuneus and left medial frontal lobe. Our results highlight the brain regions associated with the beneficiary therapeutic effects on focal to bilateral tonic–clonic seizures (thalamus and caudate) but also the undesired affective side effects of perampanel with increased anger and aggression (OFC).